The Globalization of Human Rights. - ’Bimbo OGUNBANJO; Oluseyi Elijah AKINBODE (The college of law and political science journal, 2025)
In this paper, we argue that human rights are also part of the process of globalization. Human rights are defined as socially constructed ideals of freedom and human well-being. Human rights, by their very nature and language, are universal rights. In what follows, we wish to define the process of globalization of human rights in several ways. First, we consider the successive development of different conceptions of rights from early modernity to the present. The focus here is on showing how competing definitions of human rights have evolved historically so that, when we look at the world today, we find the main conceptions of human rights in constant tension and not necessarily compatible with each other. The second part of this paper examines the globalization of rights as a process involving the transfer of universal ideas of human rights to new cultural locations and spaces. The third and final part of this paper examines the emergence of new institutional and organizational forms based on the idea of ​​human rights that function to promote human rights in a global context. These new forms are often said to constitute something called “global civil society” or “transnational cosmopolitanism.” As in other sections, we will examine this concept and ask: has globalization given rise to global civil society, and if so, what is the nature of this new entity?